Analysis of Employee Productivity of PT Pelindo Regional I Belawan After and Before Remote Working - Adawiyah, Rabiatun; Nurbaiti; Budi Dharma (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Remote Working work system at Pt Pelindo Regional I Belawan, and measure the comparison of employee productivity. This research uses a comparative qualitative approach with a focus on individuals and research subjects. Data collection methods used include in-depth interviews, observation and documentation. Data interpretation is carried out in stages, starting from data collection, data reduction, until reaching the final conclusion. Research findings show that implementing this work system has a significant impact. Employee productivity experienced a decline at the start of Covid-19 in 2020-2021 and improved again in 2022-2023 and received this category. From employee evaluation data each year including work results, time discipline, competence, attitudes, knowledge and skills required, Pt Pelindo Regional I Belawan has succeeded in facilitating employees with adequate technology so that employee productivity in implementing the Remote Working system increases.